A case of lanthanum carbonate ingestion thought to be phlebosclerotic colitis on CT imaging and abdominal radiograph. Issue 1 (February 2017) - Harris, K.; Balcam, S.
Abstract: A male admitted in the early hours of the morning, complained of a four week, right sided, non-radiating, dull and intermittent abdominal pain. Imaging suggested a diagnosis of phlebosclerotic colitis which was later discounted when the patients' history of lanthanum carbonate ingestion was examined. Phlebosclerotic colitis mostly affects the Asian population, and its cause is still not known, but can be associated with specific radiographic features. Collections of lanthanum may confuse a diagnosis of phlebosclerotic colitis as well as other factors such as voxel errors, photon starvation and movement. Highlights: PC can be non-specific, its cause unknown, diagnosis is often delayed. PC depends on specific radiographic features. Lanthanum Carbonate can collect within the lumen and confuses diagnosis. Voxel errors, photon starvation and patient movement can displace densities.